PENGEMBANGAN NILAI-NILAI ETIKA KEPERAWATAN DALAM PENDIDIKAN PANCASILA: STUDI MODEL PEMBELAJARAN DI JURUSAN KEPERAWATAN UNIVERSITAS MUHAMMADIYAH TANGERANG - Mulyawati, Linda (2017)
Penelitian ini dilatarbelakangi oleh kurang efektifnya pembelajaran Pendidikan Pancasila dalam nilai- nilai etika keperawatan. Pembelajaran yang efektif untuk mata kuliah Pendidikan pancasila adalah mata kuliah yang mampu menumbuhkan nilai adil, jujur, tanggung jawab, toleransi. Tujuan penenelitian ini adalah: (1) Menggali dan mengkaji esensi dan fungsi nilai- nilai etika keperawatan dalam Pendidikan Pancasila di Universitas Muhammadiyah Tangerang jurusan keperawatan sangat penting, (2) mengkaji Pendidikan Pancasila harus diintegrasikan dengan pengembangan nilai- nilai etika keperawatan, (3) mengkaji model pembelajaran Pendidikan Pancasila dapat mengembangkan nilai- nilai etika keperawatan, (4) mengkaji model pembelajaran Pendidikan Pancasila efektif dalam mengembangkan nilai- nilai etika keperawatan. Penelitian ini menggunakan metode penelitian kualitatif naturalistik .Teknik pengumpulan data dalam penelitian ini adalah wawancara, observasi, dan studi dokumentasi. Hasil dari penelitian ini didapatkan bahwa esensi dan fungsi nilai- nilai etika keperawatan dalam Pendidikan pancasila adalah dalam tahap awal menghadapi pasien membekali mahasiswa ditahap akademik baik afektif, kognitif, psikomtorik, sesuai dengan kompetensi dasar yang harus dicapai untuk mahasiswa pada semester yang terkait sesuai dengan kurikulum yang berlaku diorganisasi profesi maupun yang sudah dikembangkan oleh institusi dengan kurikulum penciri (sesuai visi dan misi ). Memberikan pengajaran tentang komunikasi terapeutik hal ini sangat penting untuk membangun dan memfasilitasi proses penyembuhan pasien dan etika dalam menghadapi pasien, memberikan pelayanan sesuai kemajuan Iptek yang mutakhir dilandasi etika keperawatan , hukum dan agama. ---------- This research is motivated by the less effective learning of Pancasila Education in the values of nursing ethics. Effective learning for Pancasila Education courses are courses that are able to foster fair values, honesty, responsibility, tolerance. The objectives of this research are: (1) To explore and to examine the essence and function of the values of nursing ethics in Pancasila Education at Muhammadiyah University of Tangerang of the nursing department is very important, (2) to study Pancasila Education should be integrated with the development of nursing ethics values, (3) studying the learning model Pancasila education can develop the values of nursing ethics, (4) studying the Pancasila Education lesson model is effective in developing the values of nursing ethicsThis research uses qualitative research methods naturalistic. Teknik data collection in this study are interviews, observation, and study documentation. The results of this study found that the essence and function of the values of nursing ethics in Pancasila Education is in the early stages of facing students providing students with academic stages both affective, cognitive, psychomotoric, in accordance with the basic competencies that must be achieved for students in the corresponding semester according to the curriculum which is applied professionally organized or already developed by the institution with the curriculum identifier (according to the vision and mission). Teaching about therapeutic communication is very important to build and facilitate the patient's healing process and ethics in dealing with patients, providing services according to the latest science and technology advances based on nursing, law and religion ethics. For the first time there are still nervous students who seem nervous, this can be seen when students interact with patients, there is a look of warning, there is a sentence disjointed but even though they look nervous, when viewed from the gestures they still interact with courtesy.